2020
DOI: 10.1071/an19491
|View full text |Cite
|
Sign up to set email alerts
|

A review of recent developments in the pharmacological prevention and treatment of endocrinopathic laminitis

Abstract: Despite the prevalence of endocrinopathic laminitis, the pharmacologic options for preventing and treating the disease are severely limited. The present review aims to discuss the spectrum of potential therapeutic agents for the condition, ranging from early experimental compounds to agents nearing registration. There are different pharmacologic targets for, and approaches to, managing laminitis. Reducing hyperinsulinaemia is central to diminishing endocrinopathic laminitis risk, and a detailed understanding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 100 publications
(116 reference statements)
2
6
0
Order By: Relevance
“…The improvement in laminitis in association with a reduction in insulin concentration following ertugliflozin treatment is consistent with recent research that has demonstrated a link between hyperinsulinaemia and laminitis (de Laat & Sillence, 2020). Insulin concentrations have been shown to be associated with future risk of laminitis (Knowles et al, 2021; Menzies‐Gow et al, 2017), and reduction in insulin concentration is therefore assumed to reduce the risk of clinical laminitis developing (de Laat & Sillence, 2020).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The improvement in laminitis in association with a reduction in insulin concentration following ertugliflozin treatment is consistent with recent research that has demonstrated a link between hyperinsulinaemia and laminitis (de Laat & Sillence, 2020). Insulin concentrations have been shown to be associated with future risk of laminitis (Knowles et al, 2021; Menzies‐Gow et al, 2017), and reduction in insulin concentration is therefore assumed to reduce the risk of clinical laminitis developing (de Laat & Sillence, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…The improvement in laminitis in association with a reduction in insulin concentration following ertugliflozin treatment is consistent with recent research that has demonstrated a link between hyperinsulinaemia and laminitis (de Laat & Sillence, 2020). Insulin concentrations have been shown to be associated with future risk of laminitis (Knowles et al, 2021; Menzies‐Gow et al, 2017), and reduction in insulin concentration is therefore assumed to reduce the risk of clinical laminitis developing (de Laat & Sillence, 2020). The speed and magnitude of improvement in lameness was unexpected, given that these were chronic cases; to the authors' knowledge, this is the first study to report a rapid improvement in clinical laminitis following the use of drugs that reduce insulin concentrations.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations